PENGARUH LABA AKUNTANSI, KOMPONEN ARUS KAS DAN VARIABEL EKONOMI MAKRO TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - , Rendy Valentino Manjur ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The information about stock return is required by investors in their investment decisions. Investor with rational mind always wanted to get the maximum return of investment with a certain risk. This research aimed to analyze the impact of accounting earning, operating cash flow, investing cash flow, financing cash flow, and macroeconomic variables that are oil price, exchange rate, and gold price toward mining companies stock return in Indonesia Stock Exchange. Sample in the research were 11 mining companies which listed in Indonesia Stock Exchange that were obtain by using purposive sampling method. Data in this research were secunder data which provide by financial statement from each companies, meanwhile macroeconomic variables data were provide by some websites like yahoo.finance.com, lbma.org.uk, bi.go.id, and eia.gov. Multiple linear regression with pooled data had been used to analyse data as statistic method. Dependent variable in this reasearch was stock return, meanwhile independent variables were a change in accounting earning, operating cash flow, investing cash flow, financing cash flow, oil price, exchange rate, and gold price. The finding of this research show that all independen variables have impact toward stock return. Individually, from the seven independent variables that be used in this research only investing cash flow, oil price, exchange rate, and gold price have a statistically significant impact on stock return. Overall of the independent variables could explain about 31,15 percent the variation of stock return and the rest explained by other variables about 68,85 percent.